Vernacular Translation as Enarratio Poetarum: Cædmon's “Hymn of Creation” - Kaušikaitė, Greta; Solomonik-Pankrašova, Tatyana (Respectus Philologicus, 2014)
In the Middle Ages, interpreter was thought to be a poet, skilled in the art of composition; and an exegete, able to turn the enigmatic mode of the Scriptures into the human language. Medieval translation appertained to a hermeneutical performance, with the ‘modus inveniendi’ as its constituent part. This article aims at revealing the enigmatic mode of medieval translation in Cædmon’s ‘Hymn of Creation’. Cædmon, an unenlightened cowherd, miraculously acquired the gift to recite a Christian Song, which rendered the world ‘as a Dive work of Art’. Cædmon is re–creating the original texts by imposing his ‘enarratio poetarum’ upon the Story of Creation as manifest in the ‘Book of Genesis’, the Latin ‘Vulgate’. The novelty of the research lies in deciphering the ‘enarratio poetarum’ in Cædmon’s ‘Hymn of Creation’ as a transformation from rhetorical poetics to hermeneutics, from the ‘modus inveniendi’ to the ‘modus interpretandi’, so that the Cædmonian ‘artes poetriae’ becomes inseparable from exegesis. Most previous research1 focused on the poetic vocabulary, viz., the fusion of heroic Germanic idiom and Christian lore in the context of Anglo–Latin literature. Cædmon rendered the thirty one line of Genesis, the Act of Creation, into the nine–line ‘Hymn of Creation’, which embraces not only the Act of Creation, but adores the Creator by giving Him a variety of poetic names. By re–creating the text of the Scriptures Cædmon is becoming the ‘fidus interpres’ in the sense of faithful exegete.
Keywords: medieval translation; medieval symbolism; hermeneutical performance; enarratio poetarum; allegoresis